Principles of ecotoxicology - Walker, Colin H. | Sibly, Richard M. | Peakall, D. B. | Hopkin, S. P. (Canada | CANADA Taylor & Francis / Canada, 2001)
Contents: Pollutants their fate in ecosystems; effects of pollutants on individual organisms; Effects of pollutants on populations and communities
Sin Especificar
Keywords: Contaminación-Aspectos ambientales | Ecosistemas | Toxicología